2020
DOI: 10.1111/pan.14026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between airway measurements with ultrasonography and laryngoscopy in newborns and infants

Abstract: Background: A difficult laryngoscopy in young children can be a stressful situation for the pediatric anesthetist. In recent years, several measurements have been used to obtain difficult laryngoscopy markers in children. However, there is no prospective study in which ultrasonography is expected to be used for this purpose, particularly in the newborn and infant age groups. Goals: In this study, our goal was to evaluate the relationship between the preoperative airway assessment tools and the difficult laryng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“… 17 In children between 0 and 2 years of age, an association is described between difficult laryngoscopy and body mass index (< 15.10 kg.m −2 ), thyromental distance (< 3.55 cm, a more specific parameter), mandibular length (< 6.5 cm), tragus to mouth distance (< 7.75 cm) and age less than 1 year. 18 In children under 5 years of age, the combined assessment of the lower lip-to-chin distance (< 2.2 cm), the tragus-to-mouth distance (< 3.9 cm), and low body mass index (< 12.17 kg.m −2 ) correlate with difficult glottis visualization during laryngoscopy, with high specificity and sensitivity. 15 …”
Section: Assessment Of the Child's Airwaymentioning
confidence: 99%
“… 17 In children between 0 and 2 years of age, an association is described between difficult laryngoscopy and body mass index (< 15.10 kg.m −2 ), thyromental distance (< 3.55 cm, a more specific parameter), mandibular length (< 6.5 cm), tragus to mouth distance (< 7.75 cm) and age less than 1 year. 18 In children under 5 years of age, the combined assessment of the lower lip-to-chin distance (< 2.2 cm), the tragus-to-mouth distance (< 3.9 cm), and low body mass index (< 12.17 kg.m −2 ) correlate with difficult glottis visualization during laryngoscopy, with high specificity and sensitivity. 15 …”
Section: Assessment Of the Child's Airwaymentioning
confidence: 99%
“…However, a combination of multiple ultrasound metrics and clinical examination can predict difficult laryngoscopy with greater accuracy than a single measurement alone 66 . Very few studies have evaluated difficult laryngoscopy using ultrasound in pediatric patients 69 …”
Section: Predicting Difficult Laryngoscopymentioning
confidence: 99%
“…66 Very few studies have evaluated difficult laryngoscopy using ultrasound in pediatric patients. 69 Suprahyoid Soft Tissue Indices Technique The patient is supine with the neck extended. A linear, high-frequency probe with soft tissue or musculoskeletal preset is used to obtain the required images.…”
Section: Techniquementioning
confidence: 99%
“…Ultrasound metrics evaluating anterior neck soft tissue thickness and mobility of the neck were found to be important predictors of a difficult laryngoscopy ( 96 ). To date, only one pediatric study evaluating ultrasound for difficult laryngoscopy has been performed that demonstrated good sensitivity (100%) and negative predictive value (100%) but with modest specificity (62%) and positive predictive value (19%) ( 97 ).…”
Section: Current State Of Critical Care Point-of-care Ultrasoundmentioning
confidence: 99%